Endothelial glycocalyx conditions influence nanoparticle uptake for passive targeting - Cheng MJ (Dove Medical Press, 2016)
Ming J Cheng,1 Rajiv Kumar,2 Srinivas Sridhar,1–3 Thomas J Webster,1,4 Eno E Ebong1 1Department of Chemical Engineering, 2Department of Physics, Northeastern University, 3Department of Radiation Oncology, Harvard Medical School, Boston, MA, USA; 4Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: Cardiovascular diseases are facilitated by endothelial cell (EC) dysfunction and coincide with EC glycocalyx coat shedding. These diseases may be prevented by delivering medications to affected vascular regions using circulating nanoparticle (NP) drug carriers. The objective of the present study was to observe how the delivery of 10 nm polyethylene glycol-coated gold NPs (PEG-AuNP) to ECs is impacted by glycocalyx structure on the EC surface. Rat fat pad endothelial cells were chosen for their robust glycocalyx, verified by fluorescent immunolabeling of adsorbed albumin and integrated heparan sulfate (HS) chains. Confocal fluorescent imaging revealed a ~3 µm thick glycocalyx layer, covering 75% of the ECs and containing abundant HS. This healthy glycocalyx hindered the uptake of PEG-AuNP as expected because glycocalyx pores are typically 7 nm wide. Additional glycocalyx models tested included: a collapsed glycocalyx obtained by culturing cells in reduced protein media, a degraded glycocalyx obtained by applying heparinase III enzyme to specifically cleave HS, and a recovered glycocalyx obtained by supplementing exogenous HS into the media after enzyme degradation. The collapsed glycocalyx was ~2 µm thick with unchanged EC coverage and sustained HS content. The degraded glycocalyx showed similar changes in EC thickness and coverage but its HS thickness was reduced to 0.7 µm and spanned only 10% of the original EC surface. Both dysfunctional models retained six- to sevenfold more PEG-AuNP compared to the healthy glycocalyx. The collapsed glycocalyx permitted NPs to cross the glycocalyx into intracellular spaces, whereas the degraded glycocalyx trapped the PEG-AuNP within the glycocalyx. The repaired glycocalyx model partially restored HS thickness to 1.2 µm and 44% coverage of the ECs, but it was able to reverse the NP uptake back to baseline levels. In summary, this study showed that the glycocalyx structure is critical for NP uptake by ECs and may serve as a passive pathway for delivering NPs to dysfunctional ECs. Keywords: glycocalyx, heparan sulfate, endothelial cells, NP, gold